Levels of CXCL10 Chemokine in Dengue Infected Hepatocyte Huh 7 it-1 Cell Line Co-cultured with Peripheral Blood Mononuclear Cells - BETI ERNAWATI DEWI; EVA DAMAYANTI; TJAHJANI MIRAWATI SUDIRO; AGUS SYAHRURACHMAN (Microbiology Indonesia, 2019)
Dengue is a mosquito borne virus that spreads rapidly in the world. At present, it is estimated that more than 3.9 billion people are at risk of being infected with dengue virus (DENV) and there are 96 million clinical cases that have been reported annually in 128 countries worldwide. In DENV infected patients often associated with liver dysfunction which hepatocyte and kuppfer cells as the main target of viral infections. DENV infection induced the expression of several chemokines, which might play an important role during the inflammatory response and pathogenesis of a disease. CXCL10 is known as a chemokine that activates lymphocytes for innate and adaptive immunity, induces tissue damage, and modulates tumor formation. Therefore, we conducted an in vitro study using Huh 7it-1 cells co-cultured with peripheral blood mononuclear cells (PBMCs) to investigate CXCL10 chemokine induction during DENV infection. Huh 7it-1 cells were grown on 96 micro well plate until a monolayer was formed. The cells were infected with DENV-2 at an MOI of 0.5 FFU/cell and 1 FFU/cell in the presence of PBMCs. Heat inactivated DENV-2 and Huh7 cell medium were used as control. After 2 hours of infection, cells were co-cultured with PBMCs and incubated at 37 ºC with 5% CO 2 for 48 h. Cell supernatant was collected and CXCL10 chemokine levels were measured using CXCL10 Quantikine ELISA Kit. Statistical analysis was performed by SPSS 23. In the presence of PBMCs, CXCL10 levels from DENV infected Huh 7it-1 at an MOI of 0,5 FFU/cell and MOI of 1 FFU/cell were 552,653 ± 22,779 pg  mL-1 and 576,787 ± 16,901 pg  mL-1 . Those levels were higher when compared with supernatan from heat inactivated DENV-2 and control cells. Without PBMCs, all of treatments showed lower level of CXCL10. DENV-2 infection in Huh 7it-1 cells co-cultured with PBMCs was able to induce CXCL10 secretion. Furthermore, heat inactivated DENV-2 also still capable to inducen the secretion of CXCL10 chemokine in Huh 7it-1 cells.